2022
DOI: 10.1101/2022.10.14.511731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced Folate Carrier 1 Is Present in Retinal Microvessels and Crucial for the Inner Blood Retinal Barrier Integrity

Abstract: The inner blood-retina barrier (BRB) resembles the blood-brain barrier (BBB) and is comprised of a single layer endothelium sealed with tight junctions whose abluminal surface is ensheathed by pericytes. The inner BRB is essential for providing a constant and controlled flow of nutrients and molecules to meet metabolic needs. Accordingly, the inner BRB harbors numerous carriers providing the exchange of molecules between blood and retina. One of these carriers is Reduced Folate Carrier 1 (RFC1), which function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…retinal pericytes in which they described that SLC19A1 was a pericyte marker [2]. We are thankful to these investigators for bringing this to our attention.…”
mentioning
confidence: 78%
“…retinal pericytes in which they described that SLC19A1 was a pericyte marker [2]. We are thankful to these investigators for bringing this to our attention.…”
mentioning
confidence: 78%
“…In our recent studies, where we used mice brain sections, whole-mount retinas, and retinal and cerebral microvessel isolates, we demonstrated Slc19a1 (Mus musculus symbol for SLC19A1) protein expression in mice retinal and brain microvessels. 2,3 SLC19A1 expression at the protein level had not previously been studied in the pericytes of the retina and the brain, despite its consistent detection in the transcripts of mural cells. 4 We applied commercial primary antibodies targeted to different regions-MyBioSource (MBS9134642) and Sigma-Aldrich (AV44167)-against SLC19A1 for immunohistochemistry.…”
mentioning
confidence: 99%
“…In line with the findings of Sziraki et al, we showed for the first time that Slc19a1 protein is present in the pericytes and endothelial cells of the retina comprising the inner bloodretina barrier, as well as the cerebral pericytes. 2,3 It is established in pre-clinical studies that pericytes do not have a specific marker, thus presenting certain challenges in studies focusing on their morphology and functions. The available, acceptable, and extensively used markers in literature such as platelet growth factor receptor β (PDGFR-b), NG2 (Cspg4), CD13 (aminopeptidase N), and vimentin are not entirely pericyte-specific and can only reliably identify pericytes when combined with morphological and location-based criteria.…”
mentioning
confidence: 99%